Description of Group Leader Leadership Style at PT. Antareja Mahada Makmur in Kutai Kartanegara Regency - Einsbie Grata Myn; M. Farhan As Salami (Formosa Journal of Applied Sciences, 2022)
This study aims to look at the general description of the Group Leader (GL) Leadership Style at PT. Antareja Mahada Makmur by using a behavioral analysis approach to the Path-Goal House leadership model. This type of research is descriptive qualitative, which provides an overview of the leadership style of the Group Leader (GL) using data analysis and interactive models. The research results show that the Group Leader (GL) leadership style leads to the Laissez Faire leadership style. The Path Goal House model of the eight categories found that the Group Leader (GL) behavior has carried out several categories of duties as a leader. Then the obstacle is the communication process which is still disrupted by several equipment and vehicles making a sound that is quite loud which can disrupt the smooth delivery of important information which causes a miss perception between the Group Leader (GL) and its employees and subordinates.